Analisis sport aerobik and anaerobik berbasis biomekanika - Suhartoyo, Topo; Kusuma, Mohammad Nanang Himawan; Budi, Didik Rilastiyo; Listiandi, Arfin Deri (Universitas Nusantara PGRI Kediri, 2020)
Biomechanics is a study of science that focuses on the application and analysis of laws, forms and types of movements. 100-meter run and 1,600-meter run have different motion characteristics according to body, arms and leg angles. This study aims to analyze the motion of aerobic and anaerobic exercises based on biomechanical analysis. Research methodology uses quantitative descriptive research type. The sampling technique employs purposive sampling. The population is 60 Physical Education, Sport, Health and Recreation (PJKR) students of Jenderal Sudirman University (UNSOED). Data analysis technique applies kinovea software. The results show that 1600-meter run records the body angle of 138°, leg angle of 132° and arm swing angle of 67°. While 100-meter run shows the body angle of 117°, leg angle of 137° and arm swing angle of 65°. Hence, this study concludes that the description of 100-meter run body angle is leaning 20° forward compared to 1,600-meter run, the leg angle of 100 meter run is smaller 5° compared to 1,600-meter run, and 100 meter run swing arm is smaller 2 ° compared to 1,600-meter run. Futhermore, kinovea software has capability to provide clear data based on biomechanical analysis.